Parental Corporal Punishment and Peer Victimization in Middle Childhood: A Sex-Moderated Mediation Model of Aggression - Martin, Alba; Muñoz, José Manuel; Braza, Paloma; Ruiz-Ortiz, Rosa; del Puerto-Golzarri, Nora; Pascual-Sagastizábal, Eider; Azurmendi, Aitziber; Carreras, Rosario (Frontiers in Psychology, 2021)
There is a peak in peer victimization during middle childhood, with multiple negative consequences. Parental use of corporal punishment and child aggression are the most widely-studied predictors of this phenomenon. The aim of the present study was to analyze whether parental use of corporal punishment affects peer victimization through child aggression. This mediation model was explored for both mothers and fathers and for both physical and relational forms of aggression and victimization. Furthermore, we also analyzed whether the mediation models were moderated by the sex of the child. Participants were 234 third graders (46% girls). Child aggression and victimization were measured by peers using the Mini Direct Indirect Aggression Inventory. Independent measures of mother’s and father’s use of corporal punishment were obtained from a PCA of items from the Parental Styles and Dimensions Questionnaire (PSDQ). Conditional process modeling was carried out using a macro for SPSS developed by Hayes (2013). The results revealed that aggression mediated the relationship between both father’s and mother’s use of corporal punishment and peer victimization (both physical and relational). The sex of the child was found to moderate maternal mediation models, although this was only significant for boys. Few studies to date have addressed the connection between aggressive behavior and peer victimization as outcomes of corporal punishment, taking into consideration the role of parent’s and child’s sex, and both physical and relational forms of aggression and victimization during childhood.